1991
DOI: 10.1111/j.1600-065x.1991.tb00608.x
|View full text |Cite
|
Sign up to set email alerts
|

Helper T‐Cell Subsets: Phenotype, Function and the Role of Lymphokines in Regulating their Development

Abstract: We have concentrated here on the lymphokines which might serve to regulate the different pathways of precursor development. We suggest that, as a result of antigenic stimulation, specific precursor cells both proliferate and become committed to develop into either an effector cell, a memory cell or an anergized cell. Anergy has not been dealt with in this review, but it is likely to be one of the options available. The development of an effector population takes 4-7 d (quite analogous to the time it takes for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
234
0

Year Published

1996
1996
2009
2009

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 388 publications
(245 citation statements)
references
References 61 publications
11
234
0
Order By: Relevance
“…levels of IL-7 production occur in vivo. 36 On the other hand, although mouse models have demonstrated that IL-2 and IL-4 are dispensable for appropriate lymphoid development in vivo, 15,16 these growth factors that are produced mainly by specific T-cell subsets upon activation, 37,38 play important roles in regulating T-cell function in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…levels of IL-7 production occur in vivo. 36 On the other hand, although mouse models have demonstrated that IL-2 and IL-4 are dispensable for appropriate lymphoid development in vivo, 15,16 these growth factors that are produced mainly by specific T-cell subsets upon activation, 37,38 play important roles in regulating T-cell function in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…3 We refer to the donor cells remaining 3 weeks or more after effector transfer as memory cells (16,17).…”
Section: Methodsmentioning
confidence: 99%
“…The combination of these signals leads to proliferation of naïve cells and begins the process of their differentiation to fully functional effectors capable of secreting high levels of cytokines and participating in helper and inflammatory reactions. The presence of polarizing cytokines such as IL-12 or IL-4 cause CD4 ϩ T cells to differentiate into Th1 or Th2 cells that produce distinct cytokine patterns and mediate different types of protective responses (3,4). Effector CD4 ϩ T cells are also characterized phenotypically by a decrease in the expression of CD62L and a concomitant increase in CD44 expression.…”
mentioning
confidence: 99%
“…Th1 cells, which characteristically produce IFN-g, are derived by culturing CD4 T cells with antigen in the presence of IL-12, while Th2 cells that characteristically produce IL-4, IL-5 and IL-13 are derived by culturing CD4 T cells with antigen in the presence of IL-4 (Swain et al, 1991;O'Garra and Murphy, 1994;Seder and Paul, 1994). Upon activation, Th1 cell lines undergo AICD within 12-48 h, while Th2 cell lines are significantly more resistant (Varadhachary et al, 1997;Zhang et al, 1997;Carter et al, 1998).…”
Section: Introductionmentioning
confidence: 99%